Konwergencja monetarna jako warunek wzrostu gospodarczego w nowych krajach członkowskich Unii Europejskiej - Pełka, Wanda (Monetary Convergence as a Condition of Economic Growth in the New EU Member States, 2006)
The fulfillment of the monetary convergence criteria: price stability and long-term interest rates, is a key requirement for the new EU members to join the Euro area. Last years, the increasing budget deficits characterize the economic development of Poland, Czech republic, Hungary and Slovakia. In this context the paper analyses the impact of the budget deficits on the interest rates and financial market situation. It leads to the conclusion that the governments financing the deficits on the money and capital markets determine the cost of capital for business and the possibilities for its gaining. Finally, the public debt can crowd out the investments and diminish the economic growth. For these reasons the convergence criteria cannot be dealing only as the formal conditions but the base of a macroeconomic stabilization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 63-72